Students’ Perception of the Discovery learning Strategy in Learning Reading Comprehension at Widya Manggala Senior High School - Simatupang, Bintang Ahad (JET (Journal of English Teaching), 2020)
Reading is a crucial skill for foreign language learners, and one the most learning strategy to promote reading is discovery learning. This study aimed at examining senior high school students’ perceptions of the use of the discovery learning strategy on reading comprehension. Involving 68 students of Widya Manggala Senior High School, the study collected data using a questionnaire and interviews. The quantitative data obtained from the questionnaire was analyzed by using the descriptive statistic, while the qualitative data obtained from the interview was analyzed descriptively. Findings revealed that the majority of the students have a positive and of the upper-medium level of perception of the use of the discovery learning strategy on reading comprehension. Although their perception is not very high, they realize that this strategy can make them more active and serious in the learning to read process.